Benchmarking Structural Transformation Across the World - Dabla-Norris, Era (International Monetary Fund, 2013)
This paper documents stylized facts on the process of structural transformation around the world and empirically analyzes its determinants using data on real value added by sector of economic activity (agriculture, manufacturing and services) for a panel of 168 countries over the period 1970-2010. The analysis points to large differences in sector shares both across and within regions as well as for countries at similar levels of economic development. Using both linear and quantile regression methods, it finds that a large proportion of the cross-country variation in sector shares can be accounted for by country characteristics, such as real GDP per capita, demographic structure, and population size. It also finds that policy and insitutional variables, such as product market reforms, openness to trade, human and physical capital, and finance improve the baseline model's ability to account for the variation in sectoral shares across countries